The Potency of Tradition: Turquoise, Coral, and Pearl in Sowa Rigpa (HIMALAYA, 2019)
Turquoise, coral, rubies, diamonds, amber, and pearls are among the potent substances used in Tibet’s medical traditions, specifically in ‘precious pills’ or rinchen rilbu (rin chen ril bu). Tibetan physicians use precious stones as medicines only after processing, without which none of them are considered medically beneficial. In this paper, I analyze three precious substances—turquoise, coral, and pearl—which appear together in many precious pill formulas and are processed using the same techniques. Based on textual analysis and interviews with Tibetan physicians in India, I address the questions: What makes these substances particularly ‘potent,’ expressed in the Tibetan term nüpa (nus pa)? How and why are these substances processed for use in medicines, and how is processing linked to nüpa? I argue that Tibetan medical practitioners authenticate their tradition of using precious stones as potent substances primarily through relying on authoritative texts and oral transmission, since the direct sensoexperiential understanding of the stones’ nüpa is limited compared to the more sensorial assessments of the nüpa of plants through smell and taste. Findings show that potency of precious stones emerges as a complex synergy of interactions between substances and their socio-historical, religious, economic, and political values, which are all encapsulated in ‘tradition.’ In line with Neveling and Klien (2010) and Scheid (2007), I look at tradition as a fluid process of knowledge transmission over time, and analyze what happens when practitioners try to explain the rationale behind processing practices they still meticulously follow, and how questioning, especially by foreign researchers, might influence practitioners to call on biomedical science to explain tradition.